Comparison of Antibodies with Amylase Activity from Cerebrospinal Fluid and Serum of Patients with Multiple Sclerosis - Doronin, Vasilii B. (PLoS One, 2016)
We have recently shown that IgGs from serum and cerebrospinal fluid (CSF) of MS patients are active in hydrolysis of DNA and myelin basic protein. According to literature data, anti-DNA and anti-MBP abzymes may promote important neuropathologic mechanisms in this chronic inflammatory disorder and in MS pathogenesis development. At the same time, the involvement of antibodies with amylase activity in the pathogenesis of any autoimmune disease has not yet been identified. Electrophoretically and immunologically homogeneous IgGs were obtained by a sequential affinity chromatography of the CSF proteins on protein G-Sepharose and FPLC gel filtration. We are able to present the first unpredictable evidence showing that IgGs from CSF possess amylase activity and efficiently hydrolyze maltoheptaose; their average specific Ab activity is ~30-fold higher than that of antibodies from sera of the same MS patients. Specific average RA (SAA) for IgGs from healthy volunteers was approximately ~1000 lower than that for MS patients. In addition, it was shown that a relative SAA of total proteins of CSF (including Abs) ~15-fold lower than that for purified IgGs, while the relative SAA of the total sera protein is higher than that of sera IgGs by a factor of 1033. This result speaks in favor of the fact that amylolytic activity of CSF proteins is mainly caused by the activity of amylase abzymes. One cannot exclude, that amylase abzymes of CSF can play a, as yet unknown, role in the pathogenesis of MS. Some possible reasons of these findings are discussed.